Studies on the expression of intestinal lactase in different individuals. Issue 1 (January 1995) - Harvey, C B; Wang, Y; Hughes, L A; Swallow, D M; Thurrell, W P; Sams, V R; Barton, R; Lanzon-Miller, S; Sarner, M
Abstract : Sixty one duodenal biopsy specimens were examined for the expression of lactase at the level of enzyme activity, protein, and messenger RNA. Of the 51 samples with normal villous architecture, 39 were lactase persistent, 11 were nonpersistent (adult type hypolactasia), and one was of indeterminate status. All the lactase persistent individuals showed high mRNA and a high level of the lactase protein as detected by sodium dodecyl sulphate polyacrylamide gel electrophoresis. All the 11 non-persistent individuals tested showed a low level of lactase protein. Nine of the 10 samples tested showed low mRNA and one high mRNA. These results suggest that the lactase persistence polymorphism is controlled at the level of the expression of the lactase gene, though there may be some heterogeneity of the lactase non-persistence phenotype.